THE CONDITION OF ROLLING STOCK AND REPAIR BASE IN UKRAINE - Loboiko, L. M.; Barash, Yu. S. (Science and Transport Progress, 2007)
In-process real the analysis of park of passenger carriages and base of repair of carriages is represented. Power of separate carhouses and required program of repair of Ukrzaliznitcja is represented.